AN ANALYSIS OF STUDENTS’ ABILITY AND DIFFICULTIES IN WRITING DESCRIPTIVE TEXT - Yoandita, Puri Eka; Helmie, Jauhar (Universitas Suryakancana, 2019)
AbstractThe title of this paper is An Analysis of Students' Ability and Difficulties in Writing Descriptive Text. The researcher did the research at vocational high school. This research focused on the students' ability and difficulties in writing descriptive text. Even though descriptive text is not too difficult, but many students still found it difficult. The aims of the research are to know the ability of students in writing descriptive text, to know the difficulties of students in writing descriptive text, and to know how the teacher teaches descriptive text. This is a qualitative research. In collecting the data, the researcher used text analysis, observation and questionnaire. The components of writing that are analyzed are developing the ideas, organizing of ideas, grammar, vocabulary and punctuation. The results of this study illustrate that student faced difficulties in organizing and developing ideas. They were not able to develop ideas on the texts they wrote. Whereas, in term of grammar there was no significant difficulty, they can write descriptive text by using the correct grammar. In term of vocabulary, it was difficult for students to choose appropriate vocabulary even some of them still used Bahasa Indonesia. In term of punctuation marks, there is no significant error. Based on the results of this study, it is suggested for teachers to pay attention to the teaching structure of descriptive text in the development of ideas, arrangement of ideas, grammar, vocabulary and punctuation. Teachers are also expected to provide examples and practice about the descriptive text to the students so they can achieve the purpose of education, especially in English subject.